# Complex Roots of a Quadratic Equation

In a quadratic equation with real coefficients has a complex root α + iβ then it has also the conjugate complex root α - iβ.

Proof:

To prove the above theorem let us consider the quadratic equation of the general form:

ax$$^{2}$$ + bx + c = 0 where, the coefficients a, b and c are real.

Let α + iβ (α, β are real and i = √-1) be a complex root of equation ax$$^{2}$$ + bx + c = 0. Then the equation ax$$^{2}$$ + bx + c = 0 must be satisfied by x = α + iβ.

Therefore,

a(α + iβ)$$^{2}$$ + b(α + iβ) + c = 0

or, a(α$$^{2}$$ - β$$^{2}$$ + i 2 αβ) + bα + ibβ + c = 0, (Since, i$$^{2}$$ = -1)

or, aα$$^{2}$$ - aβ$$^{2}$$ + 2iaαβ + bα + ibβ + c = 0,

or, aα$$^{2}$$ - aβ$$^{2}$$ + bα + c + i(2aαβ + bβ) = 0,

Therefore,

aα$$^{2}$$ - aβ$$^{2}$$ + bα + c = 0 and 2aαβ + bβ = 0

Since, p + iq = 0 (p, q are real and i = √-1) implies p = 0 and q = 0]

Now substitute x by α - iβ in ax$$^{2}$$ + bx + c we get,

a(α - iβ)$$^{2}$$ + b(α - iβ) + c

= a(α$$^{2}$$ - β$$^{2}$$ - i 2 αβ) + bα - ibβ + c, (Since, i$$^{2}$$ = -1)

= aα$$^{2}$$ - aβ$$^{2}$$ - 2iaαβ + bα - ibβ + c,

= aα$$^{2}$$ - aβ$$^{2}$$ + bα + c - i(2aαβ + bβ)

= 0 - i 0 [Since, aα$$^{2}$$ - aβ$$^{2}$$ + bα + c = 0 and 2aαβ + bβ = 0]

= 0

Now we clearly see that the equation ax$$^{2}$$ + bx + c = 0 is satisfied by x = (α - iβ) when (α + iβ) is a root of the equation. Therefore, (α - iβ) is the other complex root of the equation ax$$^{2}$$ + bx + c = 0.

Similarly, if (α - iβ) is a complex root of equation ax$$^{2}$$ + bx + c = 0 then we can easily proved that its other complex root is (α + iβ).

Thus, (α + iβ) and (α - iβ) are conjugate complex roots. Therefore, in a quadratic equation complex or imaginary roots occur in conjugate pairs.

Solved example to find the imaginary roots occur in conjugate pairs of a quadratic equation:

Find the quadratic equation with real coefficients which has 3 - 2i as a root (i = √-1).

Solution:

According to the problem, coefficients of the required quadratic equation are real and its one root is 3 - 2i. Hence, the other root of the required equation is 3 - 2i (Since, the complex roots always occur in pairs, so other root is 3 + 2i.

Now, the sum of the roots of the required equation = 3 - 2i + 3 + 2i = 6

And, product of the roots = (3 + 2i)(3 - 2i) = 3$$^{2}$$ - (2i)$$^{2}$$ = 9 - 4i$$^{2}$$ = 9 -4(-1) = 9 + 4 = 13

Hence, the equation is

x$$^{2}$$ - (Sum of the roots)x + product of the roots = 0

i.e., x$$^{2}$$ - 6x + 13 = 0

Therefore, the required equation is x$$^{2}$$ - 6x + 13 = 0.

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles

1. ### Types of Fractions |Proper Fraction |Improper Fraction |Mixed Fraction

Mar 02, 24 05:31 PM

The three types of fractions are : Proper fraction, Improper fraction, Mixed fraction, Proper fraction: Fractions whose numerators are less than the denominators are called proper fractions. (Numerato…

2. ### Subtraction of Fractions having the Same Denominator | Like Fractions

Mar 02, 24 04:36 PM

To find the difference between like fractions we subtract the smaller numerator from the greater numerator. In subtraction of fractions having the same denominator, we just need to subtract the numera…

3. ### Addition of Like Fractions | Examples | Worksheet | Answer | Fractions

Mar 02, 24 03:32 PM

To add two or more like fractions we simplify add their numerators. The denominator remains same. Thus, to add the fractions with the same denominator, we simply add their numerators and write the com…

4. ### Comparison of Unlike Fractions | Compare Unlike Fractions | Examples

Mar 01, 24 01:42 PM

In comparison of unlike fractions, we change the unlike fractions to like fractions and then compare. To compare two fractions with different numerators and different denominators, we multiply by a nu…